Adecuación del tratamiento de la faringoamigdalitis aguda a la evidencia científica - Ochoa Sangrador, C. (An Pediatr (Barc), 2003)
OBJECTIVE: To evaluate the appropriateness of antibiotic prescriptions in children with acute pharyngotonsillitis METHODS: A descriptive study was performed in a series of pediatric patients diagnosed with acute pharyngotonsillitis in the emergency rooms of 11 Spanish hospitals. The appropriateness of antibiotic prescriptions was assessed by comparing our clinical practice in the use of antibiotics for pharyngotonsillitis with consensus guidelines developed for this study RESULTS: We collected data from 1716 patients with acute pharyngotonsillitis. Antibiotics were prescribed in 80.9 %, mainly according to empirical criteria. The most commonly used antibiotics were amoxicillin (36 %), amoxicillinclavulanate (22.5 %), cefixime (6.6 %), azithromycin (5.8 %) and cefuroxime (5.2 %). A total of 39.5 % of the patients were aged less than 3 years, of which 75.9 % were treated empirically. Of the prescribed treatments, 22.8% were considered as the treatment of choice; 22.4 % as alternatives and 54.8 % as inappropriate CONCLUSIONS: Antibiotic treatment was prescribed in most of the cases of pharyngotonsillitis and nearly always according to empirical criteria. The number of antibiotic prescriptions was far higher than the expected cases of bacterial pharyngotonsillitis and, in many cases, the antibiotic prescriptionswere inappropriate